2002
DOI: 10.1212/wnl.59.5.762
|View full text |Cite
|
Sign up to set email alerts
|

Is a “vanishing tumor” always a lymphoma?

Abstract: The authors report clinical and radiologic characteristics and ultimate diagnosis in 12 patients with a regressing cerebral mass lesion. Primary CNS lymphoma (PCNL) was found in only half of the patients with such a lesion. In patients showing a complete resolution of the enhancing lesion the probability of finding a PCNL is smaller and survival is longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 11 publications
0
36
1
1
Order By: Relevance
“…Glucocorticoids should be withheld if possible, since lesions may disappear within a few days after treatment with steroids and biopsies may subsequently result as 'nondiagnostic'. Response to steroid treatment is not diagnostic of PCNSL, since many types of brain infiltrates improve after steroid therapy, for instance sarcoidosis, multiple sclerosis plaques and infectious lesions [23]. Optimum treatment of PCNSL remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids should be withheld if possible, since lesions may disappear within a few days after treatment with steroids and biopsies may subsequently result as 'nondiagnostic'. Response to steroid treatment is not diagnostic of PCNSL, since many types of brain infiltrates improve after steroid therapy, for instance sarcoidosis, multiple sclerosis plaques and infectious lesions [23]. Optimum treatment of PCNSL remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…As many others, I believe that detection of a "vanishing tumor" should not be considered as diagnostic of PCNSL because sarcoidosis, multiple sclerosis, acute encephalomyelitis, and other malignancies can also exhibit a dramatic response to steroids. 8 Steroid effects can interfere with histopathologic diagnosis. Although some authors reported that PCNSL can be successfully diagnosed without stopping steroids, 9 there is consensus that these drugs should be withheld in patients with a presumptive diagnosis of PCNSL until tissue is obtained, limiting its use to cases of osmotherapy inefficacy.…”
Section: Should Steroids Be Interrupted Before Biopsy?mentioning
confidence: 99%
“…2 Relapse generally occurs within 18 months in 80% of patients with PCNSL vanishing tumors, with a median remission duration of 7 months for PCNSL (range 1-54 months). 9 Late recurrence ($5 years from initial diagnosis) in appropriately treated PCNSL is a rare event. One large series identified a late relapse rate of 4% in patients who achieved CR following appropriate treatment.…”
Section: Sectionmentioning
confidence: 99%